Intersubband lifetimes in InAs/GaSb superlattices using saturated absorption spectroscopy - Poulter, A; Langerak, C; Lakrimi, M; Nicholas, R; Mason, N; Walker, P (1998)
We investigate intersubband relaxation rates above the optical phonon energy in a InAs/GaSb superlattice using saturation spectroscopy. A high-intensity free-electron laser tuned to the intersubband transition energy is used to saturate the absorption process revealing picosecond relaxation rates. The effects of the parallel magnetic field and laser energy on the relaxation processes are explored. (C) 1998 Elsevier Science B.V. All rights reserved.